5PSQ-049 Starting point to promote a potentially inappropriate prescription assessment project. (23rd March 2022) - Pons, L; Bonete, M; Campillo, J; Zayas, M; González, A; Molina, M; Barrajón, L; Bernabeu, Á; Roca, L; Aznar, MT
Abstract : Background and importance: Potentially inappropriate prescriptions (PIPs) in polymedicated elderly patients are related to adverse drug reactions, hospitalisation, increased hospital stay and higher healthcare costs. In our environment a system or a department to detect and analyse these PIPs is not available. Aim and objectives: To evaluate the prevalence and type of PIPs at hospital admission to assess whether the implementation of pharmaceutical intervention strategies in this population is useful and which ones would be the most efficient. Material and methods: Cross-sectional descriptive observational study. Patients over 65 years of age treated with ≥6 chronic drugs admitted to a tertiary hospital from 10–16 May 2021 were included. Demographic and clinical variables were recorded: age, sex, admission department, background, history of falls, pharmacological ambulatory treatment, number and type of PIPs detected, and anticholinergic burden (AB). Current ambulatory treatment was obtained by reviewing the medical records. To identify PIPs, the Screening Tool of Older Persons Prescriptions (STOPP) criteria (2014 edition Spanish version) was selected. Due to the lack of e-tools, 121 criteria could not be manually analysed in every patient, so a bibliographic search was carried out to select the 20 STOPP criteria most frequently reported in the literature. The anticholinergic burden was calculated with the Drug Burden Index (DBI) using the Anticholinergic Burden Calculator. Descriptive statistical analysis was performed with the Stata version 12.1 program. Results: 102 patients (53% women) were included. Age: 80.4±7.8 years. Pathologies/patient: 7.7±2.7. Drugs/patient: 10.2±2.9 (39% excessive polypharmacy with ≥10 drugs). Had falls: 68%. 1018 drugs were analysed. 208 PIPs (2.04±1.7 PIPs/patient) were detected. The most frequently observed PIPs were: 15% benzodiazepines ≥4 weeks, 14% drugs without indication based on clinical evidence, 9% medications with a longer duration than indicated, 8% loop diuretics in hypertension/incontinence and 8% medications that cause constipation in patients with chronic constipation. AB: 0.7±0.6. High-risk AB: 32%. Conclusion and relevance: PIPs are quite prevalent in our environment. Having tools for the systematic detection of PIPs would be very useful. These data suggest that developing a multidisciplinary pilot project, led by a pharmacist, to intervene in patients at highest risk and therefore contribute to improving the quality and safety of drug prescription would be beneficial. References and/or acknowledgements: Conflict of interest: No conflict of interest